Sickle cell disease in anaemic children in a Sierra Leonean district hospital: a case series. Issue 7 (12th July 2019) - Italia, Maria B; Kirolos, Sandy
Abstract: Sickle cell disease (SCD) is the most common inherited haemoglobinopathy wordwide, with the highest prevalence in sub-Saharan Africa. Due to the lack of national strategies and scarcity of diagnostic tools in resource-limited settings, the disease may be significantly underdiagnosed. We carried out a 6-month retrospective review of paediatric admissions in a district hospital in northern Sierra Leone. Our aim was to identify patients with severe anaemia, defined as Hb < 7 g/dl, and further analyse the records of those tested for SCD. Of the 273 patients identified, only 24.5% had had an Emmel test, among which 34.3% were positive. Furthermore, only 17% of patients with a positive Emmel test were discharged on prophylactic antibiotics. Our study shows that increased awareness of SCD symptoms is required in high-burden areas without established screening programmes. In addition, the creation or strengthening of follow-up programmes for SCD patients is essential for disease control.